Phytochemical, antimicrobial and nutritional properties of Morinda lucida benth and Nauclea latifolia leaf extracts - Enabulele, Stephen; Amusa, Oluwatosin; Uwadiae, Eseosa (International Journal of Scientific World, 2017)
The leaves of two medicinal plants namely; Morinda lucida and Nauclea latifolia were investigated for their antibacterial, mineral and phytochemical properties. Results of the study showed that the aqueous and ethanolic extract of the two leaves had significant antibacterial activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Listeria monocytogenes and Proteus mirabilis. The biologically active constituents present in the extracts were cardiac glycosides, tannins, saponin, coumarins, reducing sugar, terpenoids, alkaloids, steroids and flavonoids. The percentage yield extracts of the respective plants were Morinda lucida leaves 12.9% for ethanol and 9.0% for aqueous extracts while Nauclea latifolia had 12.1% for ethanol and 8.4% for aqueous extracts. Results of the antibacterial activity analysis revealed that the ethanolic extracts of the two medicinal plants at different concentrations were more active against the test organisms named above than the aqueous extracts. The MIC values for the ethanolic extracts ranged between 25.0 and 100.0 mg/ml while that of aqueous extract ranged between 50.0 and 100.0 mg/ml. The MBC values for ethanolic extract ranged between 50.0 and 100mg/ml while that of aqueous extracts also ranged between 50.0 and 100mg/ml. Analysis of the mineral content of the plant leaves shows that they were rich in potassium and calcium. This study confirms that the leaf extracts have some reasonable level of antimicrobial activity and appreciable amounts of mineral content which could be beneficial to human health. The findings from this work can be further exploited for isolation and characterization of novel Phytochemical compounds which could be used in the treatment of infectious diseases especially in light of the emergence of drug-resistant microorganisms and the need to produce new effective antimicrobial agents.